ISLAND Campus: a fee-free formal university educational intervention in mid- to later-life to reduce modifiable risk factors for dementia and improve cognition - Roccati, Eddy; Kitsos, Alex; Bindoff, Aidan David; Alty, Jane Elizabeth; Bartlett, Larissa; Collins, Jessica Marie; King, Anna Elizabeth; Fair, Hannah; Doherty, Kathleen; Vickers, James Clement (Frontiers in Aging Neuroscience, 2024)
IntroductionPrevious research has tended to focus on early-life education for dementia risk reduction, yet there are great gains for building cognitive reserve in mid- to later-life through educational interventions. ISLAND (Island Study Linking Ageing and Neurodegenerative Disease) Campus offered free university study to all ISLAND participants, with flexible in-person/online learning models to remove educational, socioeconomic and geographical barriers. Here the core hypothesis of ISLAND Campus was investigated: that engagement in later life education leads to improvements in modifiable risk factors for dementia, cognition and blood-based biomarkers.MethodsISLAND Campus participants were matched on age and gender to non-Campus participants via propensity score method, with optimal matching based on logistic regression. Participants completed online surveys on health, demographics, modifiable dementia risk factors via a customized Dementia Risk Profile (DRP) tool and provided blood samples for APOE genotyping and plasma phosphorylated-tau (p-tau). Cognition was measured online via the validated Cambridge Neuropsychological Test Automated Battery Paired Associates Learning (PAL) and Spatial Working Memory (SWM) tasks. Impact of the opt-in formal educational intervention was tested in R via ANCOVA.ResultsTotal participants were 986 (intervention = 492, control = 492), mean age of 61.2 years, 73.2% female, 11.7 mean years of education and 25.0% APOE e4+. Over 4 years of follow-up, intervention participants significantly improved working memory (SWM) and their risk factor profiles as measured via the DRP (p < 0.001), indicating a significant change towards lower dementia risk. Intervention and control participants were similar on socioeconomic status, location of residence, p-tau and APOE e4 presence, however Campus participants displayed a significantly higher proportion of prior university study completion (76.0%) than controls (60.0%). Intervention participants enrolled in a variety of university degrees, the most common were Diploma of Family History (n = 103, 20.9%), Diploma of Arts (n = 74, 15.0%) and Diploma of Fine Arts (n = 52, 10.5%).DiscussionISLAND Campus has shown how free later-life university education was associated with improvements in modifiable dementia risk factors over time and cognition. Given opt-in intervention participants were significantly more likely to have a prior university education, later life formal educational interventions should be targeted at individuals with lower prior education.